La Depresión Asociada al Rendimiento Académico en Adolescentes en una Institución Etno-Educativa Técnica en el municipio de Manaure La Guajira (2022)
One of the concerns presented at a global level is the low academic performance, because many countries have alarming statistics of students who fail to learn as indicated by the educational quality standards of the communities. This has as a consequence absenteeism, desertion, demotivation, failure of the school year, personal frustrations, fear of failure, economic losses to the state that invests resources in education and discontent in the family nucleus. The objective of this research was to analyze the Depression Associated with Academic Performance in Adolescents in the Technical Ethno-Educational Institution of the municipality of Manaure la Guajira, the methodology had a quantitative, non-experimental, descriptive design, with a sample of 80 students who were applied the State-Trait Depression Inventory (IDER) (Spielberger, Agudelo and Buela-Casal, 2008).